Lupus Vulgaris of the Knee in a Young Male Child: An Uncommon Location for an Uncommon Disease – A Case Report and Review of Literature - Gopal Prasad Poddar; Riya Kalawat; Moin Ahmad Siddiqui; Bhavika Bansal (Indian Journal of Paediatric Dermatology)
Lupus vulgaris (LV) is the most common form of cutaneous tuberculosis seen in India. It is a chronic and progressive infectious disease that is seen in a person with moderate to high degree of immunity. It usually originates from an underlying focus that may be present in a bone, joint, or a lymph node. It may arise by contiguous spread of the disease from underlying affected tissue, by hematogenous or by lymphatic spread. The most common sites of presentation in India are the extremities and trunk. LV of the knee is an uncommon site and is seldom reported. Here, we present the case of an 8-year-old boy with LV over the right knee.